Novel pyran based dyes for application in dye sensitized solar cells. (October 2016) - Maglione, C.; Carella, A.; Carbonara, C.; Centore, R.; Fusco, S.; Velardo, A.; Peluso, A.; Colonna, D.; Lanuti, A.; Di Carlo, A.
Abstract: A class of novel pyran based chromophores has been synthesized and characterized for what concerns their optical and electrochemical properties. The electronic structures were investigated in details by means of DFT theoretical computations. The molecular structures of the chromophores are based on a pyran core, functionalized with different electron acceptor groups, symmetrically linked to phenothiazine electron donor moieties. The dyes have different optical absorption properties, affording a set of colors ranging from orange to blue, covering most of the visible spectral region and they are characterized by high molar extinction coefficient, up to a value of 6.4·10 4  cm −1  M −1 . The dyes were used as photosensitizers in DSSC and the photovoltaic characterization of these devices was performed under simulated solar radiation. A maximum efficiency of 2.82% has been achieved. The most promising device underwent an accelerated ageing test, performed at 85 °C for 50 days: no variation of the main electrical parameters of the DSSC was observed during the test, indicating an excellent stability for devices based on this class of photosensitizers. Graphical abstract: Excellent time stability of DSSC based on pyran derivatives. Highlights: We synthesized three novel pyran based metal free photosensitizers for DSSC. Dyes show colors ranging from orange to blue, covering the most of visible spectrum. The electronic structure of the dyes were investigated at DFT level. DSSC based on the reported chromophores show power conversion efficiency up to 2.8%. Excellent device time stability determined by an accelerated aging test.